2011
DOI: 10.1080/15538605.2011.574530
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the K-12 LGBTQI Student Population in School Counselor Education Curricula: The Current State of Affairs

Abstract: A national survey of 123 school counselor educators investigated how participants integrated gay, bisexual, transgender, questioning, intersex (LGBTQI) students' needs and concerns into school counseling curricula. Results indicated 91.9% of participants integrated the K-12 LGBTQI students' needs and concerns for a median pedagogical duration of one, 3-hour session within a single course, focusing on students' knowledge and awareness of gender and sexual/affectual orientation. Follow-up interviews were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 37 publications
3
50
2
2
Order By: Relevance
“…However, the extent to which school counseling training programs are including sexual orientation is unclear despite a history of literature offering rationales and directions for doing so (Bart, 1998;Birkett et al 2009;Black, 1998;ChenHayes, 2001;Crouteau, Lark, Lidderdale, & Chung, 2005;DePaul et al, 2009;Goodrich & Luke, 2009;Logan & Barret, 2005;Luke, Goodrich, & Scarborough, 2011;Marinoble, 1998;Matthews, 2005;McFarland & Dupius, 2001;Rutter, Estrada, Ferguson, & Diggs, 2008). Chung and Brack (2005) argue that academic and clinical training programs are crucial to inclusion efforts because they represent "microsystems that mirror the counseling profession at large" (p. 205).…”
Section: School Counselor Preparationmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the extent to which school counseling training programs are including sexual orientation is unclear despite a history of literature offering rationales and directions for doing so (Bart, 1998;Birkett et al 2009;Black, 1998;ChenHayes, 2001;Crouteau, Lark, Lidderdale, & Chung, 2005;DePaul et al, 2009;Goodrich & Luke, 2009;Logan & Barret, 2005;Luke, Goodrich, & Scarborough, 2011;Marinoble, 1998;Matthews, 2005;McFarland & Dupius, 2001;Rutter, Estrada, Ferguson, & Diggs, 2008). Chung and Brack (2005) argue that academic and clinical training programs are crucial to inclusion efforts because they represent "microsystems that mirror the counseling profession at large" (p. 205).…”
Section: School Counselor Preparationmentioning
confidence: 96%
“…What commonly exists are accounts of individual school counseling educators who, often influenced by their own professional training (Luke et al, 2011), are addressing sexual orientation topics among their counseling students and within their own classes (Luke et al, 2011;McCabe & Rubinson, 2008;Whitman, 1995;Whitman, Horn, & Boyd, 2007). Typical approaches include discussions, readings, lectures, case studies, individual assignments, group work, panels, interviews, and fieldtrips.…”
Section: School Counselor Preparationmentioning
confidence: 98%
“…Only about half of students in this survey reported that they would feel comfortable speaking to school counselors or other school mental health professionals about experiences or concerns related to their identity, and only about 40% had discussed such concerns in the past. This is unsurprising, however, as research has also found that few school professionals have adequate training or professional development related to how to work with this unique population of students (Fontaine, 1998;Luke, Goodrich, & Scarborough, 2011;McCabe & Robinson, 2008). Thus, it could be argued that the beginnings of the story of invisibility start long before LGBTQQIA students enter a P-12 school.…”
Section: Contextmentioning
confidence: 92%
“…Similarly, in a national study of school counselor education programs, Luke, Goodrich, and Scarborough (2011) found little attention paid to LGBTQQIA K-12 student issues discussed in training programs, with significant knowledge gaps with the bisexual, transgender, and intersex student populations. In that same study, Luke and colleagues found that most course material related to this population was awareness-based, generally in discussions initiated by students (as opposed to introduced by the course instructor), with few practical skills-based experiences.…”
Section: Contextmentioning
confidence: 95%
“…Most counseling programs include a course on diversity; however, the emphasis in these courses seems to focus on race and ethnicity. If there is a discussion on gay and lesbian issues in counseling it is usually reserved for a single class period (Luke, Goodrich, & Scarborough, 2011). Counseling faculty can increase the amount of discussion on gay and lesbian issues in their diversity courses as well as include case studies involving gay men and lesbians in other courses where applicable.…”
Section: Implications For the Counseling Professionmentioning
confidence: 99%